Analisis Yuridis Normatif terhadap Kebijakan Sertifikat Elektronik dalam Menjamin Kepastian Hukum Hak Tanah - Lucia Setyawahyuningtyas; Cecep Tedy Siswanto (Universitas Proklamasi 45, 2025)
The purpose of this paper is to analyze the concept of electronic certificates in the Indonesian land law system and the crucial role of electronic certificate regulations in ensuring legal certainty over land rights. It also examines the status of electronic certificates as evidence of land rights. This research employs a normative juridical method. The legal materials used include primary, secondary, and tertiary sources of law. Data were collected through library research, searching for regulations, documents, doctrines, and court decisions. The discussion in this paper demonstrates that electronic certificates have the same legal force as analog certificates. Regarding the status of electronic land certificates in Indonesian land law, they serve as authentic evidence, providing legal certainty for landowners through the digitalization of land management implemented by the Complete System Registration Program (PTSL). Although electronic certificates certainly have advantages and disadvantages, integrating land policy with the Personal Data Protection Law (UU PDP) and the Electronic Information and Transactions Law (UU ITE) is essential.